1999
DOI: 10.1037/0096-1523.25.1.256
|View full text |Cite
|
Sign up to set email alerts
|

Speed, size, and edge-rate information for the detection of collision events.

Abstract: In the present study an alternative analysis to tau was considered that was based on perceived speed and size and that assumed constant deceleration for the detection of collision events. Observers were presented with displays simulating a 3-D environment with obstacles in the path of observer motion. During the trial, observer motion decelerated at a constant rate and was followed by a blackout prior to the end of the display. Observers had to detect which trials resulted in a collision. The results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
91
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(104 citation statements)
references
References 34 publications
11
91
1
1
Order By: Relevance
“…Contrastingly, the people driving in the control condition were more likely to 'slam' the brakes (at TTA = 2 s) or release the brakes (at TTA = 8 s). Our results are consistent with a study by Andersen et al (1999) in which participants non-interactively observed a scene of which the motion decelerated at a constant rate followed by a blackout of the display. Their results showed that the longer the blackout period, the less accurate participants were in determining whether they were on collision course with a stop sign.…”
Section: Tablesupporting
confidence: 95%
See 3 more Smart Citations
“…Contrastingly, the people driving in the control condition were more likely to 'slam' the brakes (at TTA = 2 s) or release the brakes (at TTA = 8 s). Our results are consistent with a study by Andersen et al (1999) in which participants non-interactively observed a scene of which the motion decelerated at a constant rate followed by a blackout of the display. Their results showed that the longer the blackout period, the less accurate participants were in determining whether they were on collision course with a stop sign.…”
Section: Tablesupporting
confidence: 95%
“…A third limitation is that the participants in our study were relatively young, with a mean age of 27 years and two thirds of them being younger than 30 years. There is some evidence that older participants make more conservative, but less accurate, decisions in braking tasks (e.g., Andersen et al, 1999;Bian & Andersen, 2014). Future research should investigate whether our results can be generalized to different age and experience levels.…”
Section: Limitations Of This Researchmentioning
confidence: 76%
See 2 more Smart Citations
“…Andersen et al (1999) tested the hypothesis that observers use to judge whether they will collide with or stop short of a stationary obstacle during a constant deceleration approach. Although judgments were highly correlated with , they were also influenced by factors that affect both perceived target distance (e.g., target size) and perceived speed of self-motion (e.g., edge rate).…”
Section: Error-nulling Models Of Brakingmentioning
confidence: 99%